Odpowiedzi

2009-12-09T16:05:01+01:00
A) p-3=1/2*R
p+r=18
p=1/2r+3
r+1/2r +3 =18
r+1/2r=15
r=10
p=5
b)
3/10n=m
m+n=65
3/10m+m=65
m=50
n=15
2009-12-09T16:05:57+01:00
P+r=18
p-0,5r=3-----------> p =3+0,5r
3+0,5r + r = 18
1,5r=15
r=10----------------> p=3+0,5*10=8
odp: p=8,r=10

m+n=65
0,3n=m

0,3n+n = 65
1,3n = 65
n=50-------------->m=0,3*50=15
1 4 1
2009-12-09T16:13:59+01:00
A)
p-3=½r
p+r=18

p-½r=3 /*2
p+r=18

2p-r=6
p+r=18

3p=24
p=8

p=8
18-8=r

p=8
r=10

b)
m=0,3n /*10 /-0,3n
m+n=65 /*3

10m-3n=0
3m+3n=195
13m=195

m=15
65-15=n

m=15
n=50